Influências institucionais, culturais e de custos de transação na escolha do modo de entrada: uma proposta para meta-análise - Novais, Ana Lúcia Moura (2013)
This research work adopts as reference the article by Brouthers awarded as the best of the decade by Journal of International Business Studies (JIBS). One of the aspects to be outlined in such text is the way Brouthers articulate a debate on institutional, cultural and transaction costs on entry mode choice by firms aiming the best performance in market. This thesis aims to investigate the actual research art involving the relationship among institutional, cultural and transaction costs aspects in international business. The discussion proposed here is justified as relevant in both academic and business environments, due to the way different authors have approached transaction costs subjects along the time. As methodological procedures, the articles were obtained in electronic databases, such as, ISI Web of Science and UMI-ProQuest. The key words were transaction cost , entry mode , cultural aspects , institutional . The selected articles were published in the period from 2002 to 2012. Articles structured in meta-analysis procedures were also selected in the referred database. All selected articles are quantitative approach, since it is an essential condition to adopt in the future meta-analytical procedures